EFEKTIVITAS ZAT PENGATUR TUMBUH DARI EKSTRAK BAWANG MERAH PADA BUDIDAYA BAWANG DAUN (ALLIUM PORUM L) - Mutryarny, Enny; Endriani, Endriani; Purnama, Indra (Jurnal Pertanian, 2022)
Leeks (Allium porum L.) have many health benefits for the human because the fiber, folic acid, calcium, potassium, and vitamin C content is relatively high in it. A study was conducted to determine plant growth regulators' (PGRs) response from shallot extract to leek crops. This study aimed to test the effectiveness of PGR from shallots at the best concentration on the growth and production of leeks. This research was performed experimentally using a non-factorial Completely Randomized Design (CRD) with five treatment levels and four replications. Each plot consists of 4 (four) plants and 2 (two) samples. The treatments were: Z0= control (without PGR), Z1= 7.5 mL of PGR shallot extract, Z2= 15 mL of PGR shallot extract, Z3= 22.5 mL of PGR shallot extract, and Z4= 30 mL of PGR shallot extract. In this study, it was found that giving PGR shallots extract to leek crops had a significant effect on the parameters of plant height, number of leaves, number of tillers, and fresh biomass. The best concentration was at a concentration of 30 mL of PGR shallot extract or Z4 treatment for all observation parameters, i.e., plant height 57.25 cm; the number of leaves 17.75 leaves; the number of tillers 5.75 tillers per hill; fresh biomass per clump 23.75 g. Z0 treatment without PGR shallot extract gave the lowest results for all parameters, such as plant height, number of leaves, number of tillers, and fresh biomass.